Analisis Pengendalian Retur Penjualan untuk Mengurangi Dampaknya pada Laba Rugi PT. Enseval Putera Megatrading Tbk, Cabang Manado - Maria Astrid Prada Lein; Inggriani Elim; Olivia Y. M Sardjono (CV. ITTC INDONESIA, 2026)
Sales returns are one of the operational risks affecting the effectiveness of internal control and a company's profit and loss. This study analyzes sales return control and its effectiveness in reducing the impact on profit and loss at PT. Enseval Putera Megatrading Tbk, Manado Branch. The research employs a qualitative descriptive method through interviews, observation, documentation, and triangulation to ensure data validity. Results show that the company has implemented sales return control through segregation of duties, an authorization system, sound operating practices, and competent employees. Overall, control over sales returns has run effectively and supports the reliability of accounting information. However, it is not yet fully optimal, as weaknesses remain in distribution, inventory monitoring, and inter-departmental coordination, causing returns due to near-expired goods or delivery errors. Sales returns reduce net sales and increase operational costs, ultimately affecting company profitability.